Optimal Control Strategies for Reducing Toxic Formation in Acetaminophen Metabolism (Journal of Nonlinear Modeling and Analysis, 2025)
Acetaminophen (N-acetyl-para-aminophenol) is the most widelyused painkiller in the world. Consuming acetaminophen involves a complexmetabolic system, since it is converted into non-toxic and toxic metabolitescalled N-acetyl-p-benzoquinone imine (NAPQI). Acetaminophen is metabolized through a series of complex metabolic processes in the liver that involveenzymes as catalysts. This study presents a metabolic analysis of acetaminophen metabolism and its optimal regulation to reduce toxin formation. Themetabolic study uses kinetic modeling combined with metabolic control analysis to identify key enzymes that can be modified to reduce hepatotoxicitydue to excessive drug consumption. The sensitivity result shows that cytochrome (CYP) and uridine 5’-diphosphate-glucuronosyltransferase (UGT)are the two key enzymes that can be considered as internal control parameters. By inhibiting the reaction rate of CYP and UGT, the formation ofN-acetyl-p-benzoquinone imine (NAPQI) can be reduced up to 69.9%, andthe formation of Acetaminophen-Glucuronide (APAP-G) can be increased byapproximately 0.49% such that Acetaminophen in the liver (APAP-L) can beexcreted directly into the urine. Increasing the concentration of antioxidantGSH can also prevent hepatotoxicity by forming the complex NAPQI-GSH sothat hepatotoxicity due to overconsumption of acetaminophen can be reduced.